2014
DOI: 10.1186/1472-6882-14-43
|View full text |Cite|
|
Sign up to set email alerts
|

A double-blind, randomized clinical trial of dietary supplementation on cognitive and immune functioning in healthy older adults

Abstract: BackgroundDeclining cognitive function is relatively common and increasingly prevalent. Studies have shown that different nutrients (e.g., Ginkgo biloba and vitamin E) appear to be effective at improving memory and concentration, while less is known about their effect on immunity.MethodsThis study investigated the effect of Ginkgo Synergy® plus Choline (n = 33) and OPC Synergy® plus Catalyn® (n = 31) versus placebo (n = 33) in a 6-month, randomized, double-blind trial on cognitive and immune functioning among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…However, for studies of combination products, four studies reported mild adverse events of C. asiatica -containing products. Two studies reported adverse event rates comparable to the placebo rate 31 , 34 , while another two studies reported lower rates of adverse event for C. asiatica -containing products 30 , 33 . Common adverse events were gastrointestinal discomfort, flatulence, nausea, headache, decreased appetite, sedation, and rash.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, for studies of combination products, four studies reported mild adverse events of C. asiatica -containing products. Two studies reported adverse event rates comparable to the placebo rate 31 , 34 , while another two studies reported lower rates of adverse event for C. asiatica -containing products 30 , 33 . Common adverse events were gastrointestinal discomfort, flatulence, nausea, headache, decreased appetite, sedation, and rash.…”
Section: Resultsmentioning
confidence: 92%
“…The combination of C. asiatica with other herbs also showed non-significant improvements in overall cognitive function. However, the combination products in other studies have revealed that there arepossible effects on attention and concentration 30 , executive function 34 and information processing speed 30 . The improvement in cognitive function from the combination products might be due to the synergistic effects of C. asiatica with other herbs or the effects of other herbs in C. asiatica -containing products such as G. biloba 31 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed improvements in cognitive and immune functioning and inflammation in persons with Alzheimer's disease in response to a dietary supplement containing multiple nutrients, such as polysaccharides, antioxidants, and omega-3 fatty acids, among others [19]. We also found that the combination of gingko biloba and choline produced modest improvements in cognitive functioning and inflammation in a sample of healthy elderly adults [20]. Thus, the continued investigation of multi-component formulations is warranted inasmuch as these studies provide the opportunity to evaluate a model of synergism among a complex of vitamins, minerals, phytonutrients, and co-factors.…”
Section: Introductionmentioning
confidence: 80%
“…Incorporating cognition, immunity, metabolism and psychological functions into this global index may be meaningful for dietary supplements with multifaceted effects. For example, supplementation with a blend of phytochemicals and choline, altered epidermal growth factor (EGF), an immune function marker, along with improvements in cognition [ 52 ]. Supplementation with omega-3 fatty acids enhanced cognition and cerebral blood flow, particularly in the prefrontal cortex, in comparison to the placebo assessed by near-infrared spectroscopy during cognition testing [ 53 ].…”
Section: A Global Index For Cognitive Healthmentioning
confidence: 99%